Lithium and age of pre-main sequence stars: the case of Parenago 1802. (April 2016) - Giarrusso, M; Tognelli, E; Catanzaro, G; Degl'Innocenti, S; Dell'Omodarme, M; Lamia, L; Leone, F; Pizzone, R G; Prada Moroni, P G; Romano, S; Spitaleri, C
Abstract: With the aim to test the present capability of the stellar surface lithium abundance in providing an estimation for the age of PMS stars, we analyze the case of the detached, double-lined, eclipsing binary system PAR 1802. For this system, the lithium age has been compared with the theoretical one, as estimated by applying a Bayesian analysis method on a large grid of stellar evolutionary models. The models have been computed for several values of chemical composition and mixing length, by means of the code FRANEC updated with the Trojan Horse reaction rates involving lithium burning.